A novel lineage of the Capra genus discovered in the Taurus Mountains of Turkey using ancient genomics - Kevin G Daly; Benjamin S Arbuckle; Conor Rossi; Valeria Mattiangeli; Phoebe A Lawlor; Marjan Mashkour; Eberhard Sauer; Joséphine Lesur; Levent Atici; Cevdet Merih Erek; Daniel G Bradley (eLife, 2022)
Direkli Cave, located in the Taurus Mountains of southern Turkey, was occupied by Late Epipaleolithic hunters-gatherers for the seasonal hunting and processing of game including large numbers of wild goats. We report genomic data from new and published Capra specimens from Direkli Cave and, supplemented with historic genomes from multiple Capra species, find a novel lineage best represented by a ~14,000 year old 2.59 X genome sequenced from specimen Direkli4. This newly discovered Capra lineage is a sister clade to the Caucasian tur species (Capra cylindricornis and Capra caucasica), both now limited to the Caucasus region. We identify genomic regions introgressed in domestic goats with high affinity to Direkli4, and find that West Eurasian domestic goats in the past, but not those today, appear enriched for Direkli4-specific alleles at a genome-wide level. This forgotten ‘Taurasian tur’ likely survived Late Pleistocene climatic change in a Taurus Mountain refuge and its genomic fate is unknown.